2010
DOI: 10.1021/ja104848m
|View full text |Cite
|
Sign up to set email alerts
|

[MnIII4LnIII4] Calix[4]arene Clusters as Enhanced Magnetic Coolers and Molecular Magnets

Abstract: The use of methylene-bridged calix[4]arenes in 3d/4f chemistry produces a family of clusters of general formula [Mn(III)(4)Ln(III)(4)(OH)(4)(C4)(4)(NO(3))(2)(DMF)(6)(H(2)O)(6)](OH)(2) (where C4 = calix[4]arene; Ln = Gd (1), Tb (2), Dy (3)). The molecular structure describes a square of Ln(III) ions housed within a square of Mn(III) ions. Magnetic studies reveal that 1 has a large number of molecular spin states that are populated even at the lowest investigated temperatures, while the ferromagnetic limit S = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
117
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 281 publications
(120 citation statements)
references
References 52 publications
2
117
1
Order By: Relevance
“…Calculating the entropy changes obtained from the magnetization data ( Figure 3) gives values at 3 K and for a field change DH = 70 kG of: for 1, 26.5; for 2, 12.2; for 3, 5.6 J kg À1 K À1 . The entropy change of 1 is much larger than the value reported for previous 3d-4f compounds at 4 K [5,13] and slightly higher than the highest value reported (25 J kg À1 K À1 ) for a {Mn 14 } cage.…”
Section: Emu K Molcontrasting
confidence: 61%
“…Calculating the entropy changes obtained from the magnetization data ( Figure 3) gives values at 3 K and for a field change DH = 70 kG of: for 1, 26.5; for 2, 12.2; for 3, 5.6 J kg À1 K À1 . The entropy change of 1 is much larger than the value reported for previous 3d-4f compounds at 4 K [5,13] and slightly higher than the highest value reported (25 J kg À1 K À1 ) for a {Mn 14 } cage.…”
Section: Emu K Molcontrasting
confidence: 61%
“…[6][7][8][9] The synthesis of molecules combining the magnetic moment and relatively strong exchange interactions of 3d transition metals (M) with the anisotropy naturally provided by lanthanide (Ln) ions is especially promising. Several molecular clusters of this type have been reported, such as {Mn 4 Ln 4 }, 10 {Mn 12 Gd}, 11 and {Cr 4 Dy 4 }, 12 with Ln = heavy Ln's, and {Mn 11 Ln 2 }, 13,14 with Ln = light rare earths. It was found that, in particular, Dy(III) ions are very useful for introducing anisotropy into these molecules, 15 thus confirming the possibility of achieving increased anisotropy in the lanthanide-transition-metal molecular combination.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, they emerged as perspective components for information storage 3 , quantum computing 4 , spintronics 5 , and magnetic refrigeration 6,7 . A necessary condition for a compound to be an SMM is a large axial magnetic anisotropy D that splits the energy levels of a metal ion under zero magnetic field and gives rise to an energy barrier between the states with opposite directions of the magnetic moment U = |D|S 2 (or, for non-integer S, U = |D|(S 2 -1/4)).…”
mentioning
confidence: 99%